Preparation method of air cathode catalyst Co-NC-x of microbial fuel cell
Through the preparation method of Co-NC-x cathode catalyst, the hydrophobic modification technology of ZIF-67 derived carbon and 3,5-bis(trifluoromethyl)aniline was used to solve the weak oxygen mass transfer of the air cathode catalyst of microbial fuel cell. The problem is that the oxygen reduction reaction efficiency and battery performance are improved, and low-cost and efficient catalyst replacement is achieved.
Patent Information
- Application Number
- CN202410535497.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-30
- Publication Date
- 2024-12-17
AI Technical Summary
The oxygen reduction reaction efficiency of existing microbial fuel cell air cathode catalysts is low, resulting in poor battery performance, especially the problems of weak oxygen mass transfer and low power production performance.
Using the preparation method of Co-NC-x cathode catalyst, conductivity and stability composite materials are prepared by ultrasonic dispersion, calcination and hydrophobic modification technology, and ZIF-67 derived carbon and 3,5-di(trifluoromethyl) are used. The surface grafting modification of the catalyst is improved by improving the hydrophobicity and oxygen transfer efficiency.
It significantly improves the oxygen reduction reaction rate and battery performance, reduces the catalyst production cost, and achieves power production performance better than Pt/C catalysts, and is suitable for large-scale production applications.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a cathode catalyst Co-NC-x for a microbial fuel cell. Background Art
[0002] Microbial fuel cells (MFCs) have attracted widespread attention due to their unique dual functions of obtaining electricity from organic matter and treating wastewater at the same time. They can not only generate electricity while treating wastewater, but also have the advantages of wide raw material sources, low cost, good safety performance, clean and environmentally friendly. Therefore, it has broad application prospects in the fields of wastewater treatment and new energy development, and is of great significance in treating pollutants and providing new energy. Single-chamber microbial fuel cells (SCMFCs) are the most widely used configuration in this type of fuel cell due to their simple structure, convenient operation, low reactor cost, and high efficiency. According to past studies, the air cathode has a significant effect on the performance of SCMFCs, especially in the oxygen reduction reaction (ORR) occurring at the cathode. The stronger the ORR activity of the catalyst means the stronger the performance of the SCMFCs. At present, the most commonly used ORR catalyst is the commercial Pt / C catalyst, but its high price and poor operating stability limit the large-scale use of SCMFCs, so finding a catalyst that can perfectly replace Pt / C has become a significant task.
[0003] The oxygen reduction reaction (ORR) kinetics of the air cathode is closely related to the electrochemical performance of MFCs. The oxygen reduction reaction at the cathode occurs at the solid-gas three-phase interface. As the ORR at the cathode proceeds, liquid water may accumulate in the mass transfer pores of the gas diffusion layer, hindering the diffusion of O2 to the active site, thereby affecting the reaction efficiency. Using hydrophobic agents such as PTFE to change the hydrophilicity of the electrode is a common method to inhibit the "flooding" phenomenon. However, the place where ORR actually occurs and the location that is severely affected by the "flooding" phenomenon is the active site, which can be regarded as a catalyst on the electrode. In other words, it is not enough to simply hydrophobically modify the electrode, and consideration should be given to making the catalyst itself able to inhibit "flooding". The essence of the "flooding" phenomenon that causes the battery performance to decline is that the three-phase interface at the reaction site is destroyed, and the O2 mass transfer changes from the original efficient gas phase mass transfer to slow dissolved oxygen liquid phase mass transfer. Hydrophobic modification of the catalyst itself can effectively inhibit the active site from being flooded, and hydrophobicity often enhances the gas affinity of the material, resulting in an increase in the O2 concentration at the active site and thus an increase in the ORR reaction rate.
[0004] For the air cathode, the electrode must have good catalytic activity and high oxygen transfer efficiency, which can be achieved by hydrophobic modification of the air cathode catalyst and preparation of hydrophilic and hydrophobic materials. Hydrophobic modification of materials can increase the concentration of O2 near the active site. According to the chemical reaction kinetics, the higher the substrate concentration, the faster the chemical reaction. Therefore, the present invention aims to invent a method for preparing and modifying the cathode catalyst Co-NC-x, so as to achieve hydrophobic modification of the catalyst and thus accelerate the reaction rate of ORR at the cathode. Summary of the invention
[0005] The purpose of the present invention is to solve the problem in the prior art that the air cathode has low electricity generation performance and weak oxygen mass transfer, resulting in low ORR efficiency, and to provide a method for preparing a catalyst suitable for the air cathode of a microbial fuel cell. The method of preparing a microbial fuel cell air cathode catalyst of the present invention is characterized in that the preparation method of the microbial fuel cell air cathode material is achieved by the following steps:
[0006] (1) Preparation of Co-NC-x cathode catalyst: ① Dissolve a certain amount of 2-methylimidazole in deionized water and disperse by ultrasonic to obtain a uniformly dispersed solution; ② Dissolve a certain amount of cobalt acetate in deionized water and disperse by ultrasonic to obtain a uniformly dispersed solution; ③ Add the solution obtained in step ② dropwise to the solution obtained in step ① to obtain a mixed solution; ④ Stir the solution obtained in step ③ and let it stand, wash it with ethanol and then dry it to obtain ZIF-67; ⑤ Place the product ZIF-67 obtained in step ④ in a tubular furnace, calcine it for a certain period of time under a nitrogen atmosphere, and then cool it naturally to room temperature to obtain ZIF-67 derived carbon; ⑥ Add a certain volume of 3,5 -bis(trifluoromethyl)aniline is fully dissolved in the ethanol solution and ultrasonically dispersed to obtain a uniformly dispersed solution; ⑦ the solution obtained in step ⑥ is mixed with deionized water and the product ZIF-67 derived carbon obtained in step ⑤ and then ultrasonically dispersed to obtain a solution; ⑧ sodium nitrite is added to deionized water to obtain the desired solution; ⑨ hydrochloric acid is added to the solution obtained in step ⑦, and then the solution obtained in step ⑧ is added thereto to obtain a mixture, which is ultrasonicated for 1 hour and then allowed to stand for 1 hour; ⑩ the product obtained in step ⑨ is washed with deionized water and ethanol respectively, and then dried to obtain the modified catalyst material Co-NC-x for the air cathode, thereby completing the preparation of the air cathode catalyst for the microbial fuel cell.
[0007] (2) Preparation of Co-NC-x cathode electrode and assembly of single-chamber MFC reactor: The present invention adopts an air cathode single-chamber microbial fuel cell reactor with a volume of 28 mL. The anode is a fluffy carbon fiber brush with a large specific surface area. The steps of pretreating the carbon fiber brush are to soak it in acetone for 24 hours to remove organic impurities on the surface, and then rinse it with water and ethanol for multiple times. Finally, it is placed in a muffle furnace and calcined at 450°C for 1 hour to increase the mechanical strength. The composition of the air cathode includes an electron collector, a catalyst layer and a gas diffusion layer. Similarly, the 60-mesh stainless steel mesh used as the current collector is first cleaned with acetone to remove impurities, rinsed with ethanol and water, and then placed in an oven to dry for use. Then, the conductive carbon powder and 60% polytetrafluoroethylene (PTFE) dispersion are uniformly mixed in ethanol, stirred into a mud-like substance at a mass ratio of 3:7, and then the electrode mud and the stainless steel mesh are pressed together with an electric roller press to form a gas diffusion layer. Then, it is placed in a muffle furnace at 340°C and calcined for 20 minutes to melt the PTFE to form a gas mass transfer channel. On the other side, the prepared catalyst and PTFE were mixed in a mass ratio of 1:1, and the catalyst layer was pressed onto a stainless steel mesh and dried in an oven in a similar way to the gas diffusion layer. The cathode was cut into discs with a diameter of 30 mm. When assembling the reactor, the gas diffusion layer was facing outward, so that more oxygen could contact the catalyst layer, which was beneficial to the reaction.
[0008] Preferably, in step (1)①, the amount of 2-methylimidazole used is 6.72 g, and the amount of deionized water used is 15 mL.
[0009] Preferably, the amount of cobalt acetate used in step (1) ② is 1.80 g, and the amount of deionized water used is 15 mL.
[0010] Preferably, in step (1) ④, after stirring for 10 minutes, the mixture is allowed to stand for 5 hours, washed with ethanol 6 times, and the product is placed in an oven at 60° C. and dried for 12 hours.
[0011] Preferably, the calcination process in step (1) ⑤ is to increase the temperature from room temperature to 700° C. at a heating rate of 3° C. / min and calcine at a constant temperature for 1 hour.
[0012] Preferably, in step (1)⑥, the certain volumes are 0.5, 1.0, 1.5, 2.0, 2.5, 3.0 µL, respectively, and the amount of ethanol used is 5 mL.
[0013] Preferably, in step (1) ⑦, the amount of deionized water used is 60 mL, and the amount of ZIF-67 derived carbon used is 0.1 g.
[0014] Preferably, in step (1)⑧, the amount of deionized water used is 5 mL, and the amount of sodium nitrite used is 0.01 g.
[0015] Preferably, the amount of 0.5M hydrochloric acid used in step (1) ⑨ is 2 mL.
[0016] Preferably, in step (1) (10), the product is washed with deionized water three times and then with ethanol three times, and the product is dried in an oven at 60° C. for 12 hours.
[0017] Compared with the prior art, the advantages of the present invention are:
[0018] (1) The Co-NC-x microbial fuel cell cathode catalyst material prepared by the method of the present invention uses ZIF-67 derived carbon with oxygen reduction performance as a base material for surface grafting modification to obtain a composite material with good conductivity, stability and high catalytic activity;
[0019] (2) The Co-NC-x microbial fuel cell cathode catalyst material prepared by the method of the present invention uses inexpensive 3,5-di(trifluoromethyl)aniline as a hydrophobic modifier, and the dosage is extremely low, thus saving costs;
[0020] (3) The Co-NC-x microbial fuel cell cathode catalyst material prepared by the method of the present invention achieves high oxygen reduction performance through micro-interface regulation of the reaction by hydrophobic modification, thereby obtaining power generation performance that is superior to that of precious metal catalysts such as Pt / C, effectively reducing the catalyst production cost and providing a theoretical basis for the large-scale production and application of microbial fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Contact angle diagrams of Co-NC-9.0 (a); Co-NC-31.6 (b); Co-NC-64.4 (c); Co-NC-90.4 (d); Co-NC-131.4 (e); Co-NC-144.8 (f) and Co-NC-153.4 (g);
[0022] Figure 2 is the SEM image of Co-NC-x catalyst;
[0023] Figure 3 is the cyclic voltammetry curve of Co-NC-x catalyst;
[0024] Figure 4 is the linear sweep voltammetry curve of Co-NC-x catalyst;
[0025] Figure 5 The underwater contact angle diagram of Co-NC-x catalyst;
[0026] Figure 6 Electrochemically active surface area (ECSA) of Co-NC-x catalysts versus underwater bubble disappearance velocity (a) and limiting current density (b);
[0027] Figure 7is the voltage-time relationship diagram of Co-NC-x catalyst;
[0028] Figure 8 Polarization curve-power density curve of Co-NC-9.0 and Co-NC-131.4 catalysts;
[0029] Fig. 9 Figure 2 shows the COD removal rate and coulombic efficiency of Co-NC-x catalyst. DETAILED DESCRIPTION Specific implementation method one:
[0031] (1) Preparation of Co-NC-x cathode catalyst ① Dissolve 6.72 g of 2-methylimidazole in 15 mL of deionized water and disperse by ultrasonication to obtain a uniformly dispersed solution; ② Dissolve 1.80 g of cobalt acetate in 15 mL of deionized water and disperse by ultrasonication to obtain a uniformly dispersed solution; ③ Add the solution obtained in step ② dropwise to the solution obtained in step ① to obtain a mixed solution; ④ Stir the solution obtained in step ③ for 10 minutes and then let it stand for 5 hours. After washing with ethanol 6 times, place the product in a 60°C oven and dry it for 12 hours; ⑤ Place the product obtained in step ④ in a tubular furnace at 700°C in a nitrogen atmosphere at a heating rate of 3°C / min and calcine it for 1 hour, then cool it for use; ⑥ Add 0 .5µL of 3,5-di(trifluoromethyl)aniline was dissolved in 5mL of ethanol and ultrasonically dispersed to obtain a uniformly dispersed solution; ⑦ The solution obtained in step ⑥ was mixed with 60mL of deionized water and 0.1g of the product obtained in step ⑤ and ultrasonically dispersed to obtain a solution; ⑧ 0.01g of sodium nitrite was added to 5mL of deionized water to obtain a solution; ⑨ 2ml of 0.5M hydrochloric acid was added to the solution obtained in step ⑦, and then the solution obtained in step ⑧ was added thereto to obtain a mixture, which was ultrasonically dispersed for 1 hour and then allowed to stand for 1 hour; ⑩ The product obtained in step ⑨ was washed with deionized water and ethanol respectively, and the product was placed in an oven at 60°C for 12 hours to obtain a modified catalyst material for the air cathode.
[0032] (2) Preparation of Co-NC-x cathode electrode and assembly of single-chamber MFC reactor: The present invention adopts an air cathode single-chamber microbial fuel cell reactor with a volume of 28 mL. The anode is a fluffy carbon fiber brush with a large specific surface area. The steps of pre-treating the carbon fiber brush are to soak it in acetone for 24 hours to remove organic impurities on the surface, and then rinse it with water and ethanol for multiple times. Finally, it is placed in a muffle furnace and calcined at 450°C for 1 hour to increase the mechanical strength. The steps of composing the air cathode are to first clean the 60-mesh stainless steel mesh used as the current collector with acetone to remove impurities, rinse it with ethanol and water, and then put it in an oven to dry for use. Then, the conductive carbon powder and 60% polytetrafluoroethylene (PTFE) dispersion are uniformly mixed in ethanol, stirred into a mud-like substance at a mass ratio of 3:7, and then the electrode mud and the stainless steel mesh are pressed together with an electric roller press to form a gas diffusion layer. Then, it is placed in a muffle furnace at 340°C and calcined for 20 minutes to melt the PTFE to form a gas mass transfer channel. On the other side, the prepared catalyst and PTFE were mixed in a mass ratio of 1:1, and the catalyst layer was pressed onto a stainless steel mesh and dried in an oven in a similar way to the gas diffusion layer. The cathode was cut into discs with a diameter of 30 mm. When assembling the reactor, the gas diffusion layer was facing outward, so that more oxygen could contact the catalyst layer, which was beneficial to the reaction.
[0033] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that the volume of 3,5-di(trifluoromethyl)aniline in step (1)⑥ is 1.0 μL. The other steps and parameters are the same as those in specific embodiment 1.
[0034] Specific embodiment 3: This embodiment differs from specific embodiment 1 in that the volume of 3,5-di(trifluoromethyl)aniline in step (1)⑥ is 1.5 μL. The other steps and parameters are the same as those in specific embodiment 1.
[0035] Specific embodiment 4: This embodiment differs from the specific embodiment 1 in that the volume of 3,5-di(trifluoromethyl)aniline in step (1)⑥ is 2.0 μL. The other steps and parameters are the same as those in the specific embodiment 1.
[0036] Specific embodiment 5: This embodiment differs from specific embodiment 1 in that the volume of 3,5-di(trifluoromethyl)aniline in step (1)⑥ is 2.5 μL. The other steps and parameters are the same as those in specific embodiment 1.
[0037] Specific embodiment 6: This embodiment is different from the specific embodiment 1 in that the volume of 3,5-di(trifluoromethyl)aniline in step (1)⑥ is 3.0 μL. The other steps and parameters are the same as those in the specific embodiment 1.
[0038] Specific embodiments 1 to 6 of the catalytic materials and their corresponding characterization and performance analysis:
[0039] Figure 1 It is the contact angle of the Co-NC-x series catalysts. It can be directly observed that the contact angle of the unmodified ZIF-67-derived carbon is 9°, which is a super hydrophilic material with high surface energy. With the increase of the amount of hydrophobic agent, the surface energy of the modified ZIF-67-derived carbon gradually increases, and the contact angle also gradually increases, which are 31.6°, 64.4°, 90.4°, 131.4°, 144.8° and 153.4° respectively. The gradual increase in the contact angle proves that the materials we synthesized have become more and more hydrophobic, indicating that a series of composite materials with different hydrophilicity and hydrophobicity have been successfully prepared.
[0040] Figure 2 This is a SEM image. We can see that the series of materials are all rough-surfaced rhombic dodecahedrons with diameters of about 700-800nm. The low-magnification SEM image in the figure proves that our series of materials are similar in size, uniform in size, and have basically the same surface roughness.
[0041] Figure 3 The CV curves of Pt / C and Co-NC-x (x=9.0, 31.6, 64.4, 90.4, 131.4, 144.8 and 153.4) in 0.05MPBS are shown in the figure. As shown in the figure, the series of materials have a reduction peak between 0.80-0.86V, which symbolizes ORR, and the peak positions are higher than those of Pt / C catalyst.
[0042] Figure 4 The LSV curve in 0.05 M PBS (5 mV s -1 and 1600 rpm), it can be observed that Co-NC-131.4 has the highest half-wave potential (E 1 / 2 ) is 0.8677 V, which is much higher than Pt's 0.8462 V, indicating that Co-NC-131.4 has ORR performance far beyond Pt / C. At the same time, the limiting current of Co-NC-131.4 is significantly higher than that of other catalysts. This phenomenon may be due to the interface regulation of the material after hydrophobic modification, which allows more O2 to gather around the active sites.
[0043] Figure 5 This is an underwater contact angle graph. Hydrophobicity will make the material gas-friendly. It is speculated that the hydrophobic modification will increase the affinity of the material to O2, resulting in faster reaction kinetics. In order to verify the hypothesis, an underwater contact angle test was designed. Figure 5As shown in the figure, as the hydrophobicity of the catalyst increases, the angle of the bubble when it first contacts the material is getting smaller. As time goes by, the more hydrophobic the catalyst, the faster the bubbles disappear. It can be understood that under normal circumstances, the bubbles are only pushed into the catalyst sheet by water pressure. The bubble size is 10µL, so the water pressure they are subjected to is the same. If the catalyst has an affinity for oxygen in the air, then in addition to the water pressure, there is still an upward force that makes it easier for the bubbles to be pressed into the sheet. Therefore, as the hydrophobicity increases, the catalyst's affinity for oxygen also increases.
[0044] Figure 6 The graphs of the electrochemically active surface area (ESCA) of the catalyst series, the underwater bubble disappearance rate (a) and the limiting current density (b) are shown in Figure 1. Combining the above content, the electrochemically active surface area (ECSA) is calculated and it is found that its value decreases with the increase of hydrophobicity. Combined with the enhancement of oxygen mass transfer by hydrophobicity described above, we get Figure 6 (a). The increase in catalyst hydrophobicity will increase the contact area between the gas phase and the catalyst surface, resulting in faster O2 mass transfer. However, an overly hydrophobic catalyst surface will reduce the contact area between the electrolyte and the catalyst, weakening the ion mass transfer in the liquid phase. The results are shown in Figure 2. Figure 6 As shown in (b), as the hydrophobicity of the catalyst increases, the limiting current density of its ORR increases first and then decreases.
[0045] Figure 7 It is a schematic diagram of the voltage output of single-chamber MFCs of Co-NC-9.0 and Co-NC-131.4 catalysts, showing the voltage output performance of Co-NC-9.0 and Co-NC-131.4 catalysts during the 1000-hour test period under the condition of 1000Ω external resistance. It can be directly seen from the figure that the voltage of the unmodified Co-NC-9.0 catalyst has decreased, which may be attributed to the pseudographite-wrapped metal structure effectively preventing the metal nanoparticles from falling off as catalytic sites. Nevertheless, the mass transfer barrier caused by excessive microbial growth still exists. The Co-NC-x series samples showed slight fluctuations in stability, which may be due to the role of hydrophobic modification in suppressing mass transfer problems caused by microbial contamination. The output voltage of Co-NC-131.4 is higher than that of Co-NC-9.0, which is due to the hydrophobic effect that makes the O2 mass transfer at the cathode smoother, thereby accelerating the ORR process.
[0046] Figure 8 The polarization curve and power density curve of the final cycle are shown in Figure 2. The maximum power density of SCMFCs using Co-NC-131.4 as the cathode catalyst reached 835.002 mW m -2 , which is higher than 307.641 mW m of Pt / C. -2There is a significant improvement, indicating that Co-NC-131.4 still exhibits excellent ORR activity in SCMFCs at the end of operation.
[0047] Fig. 9 It is the COD removal rate and coulomb efficiency of the final cycle. The coulomb efficiency (CE) is calculated by the COD removal rate and output voltage to study the efficiency of the electron cycle. According to the data in the figure, the reactor using Co-NC-131.4 as the cathode showed the highest COD removal efficiency (95.43%), which exceeded the COD removal rate of Pt / C (89.56%). The COD removal rate reflects the effect of the anode in the reactor on the degradation of organic matter in the electrolyte. The measured COD removal efficiency is consistent with the voltage output and power density data obtained previously.
Claims
1. A method for preparing an air cathode catalyst for a microbial fuel cell, characterized in that The preparation of the air cathode material of the microbial fuel cell is achieved through the following steps: (1) Preparation of Co-NC-x cathode catalyst: ① Dissolve a certain amount of 2-methylimidazole in deionized water, ultrasonically disperse, and obtain a uniformly dispersed solution; ② Dissolve a certain amount of cobalt acetate in deionized water, ultrasonically disperse, and obtain a uniformly dispersed solution; ③ Add the solution obtained in step ② dropwise to the solution obtained in step ① to obtain a mixed solution; ④ Stir the solution obtained in step ③ and let it stand, wash it with ethanol, and then dry it to obtain ZIF-67; ⑤ Place the product ZIF-67 obtained in step ④ in a tubular furnace, calcine it for a certain period of time under a nitrogen atmosphere, and then naturally cool it to room temperature to obtain ZIF-67 derived carbon; ⑥ Add x 7. Dissolve 3,5-di(trifluoromethyl)aniline in ethanol and disperse by ultrasonic to obtain a uniformly dispersed solution; 8. Mix the solution obtained in step 6 with deionized water and the product ZIF-67 derived carbon obtained in step 5 and then ultrasonic to obtain a solution; 9. Add sodium nitrite to deionized water to obtain a solution; 10. Add hydrochloric acid to the solution obtained in step 7 and then add the solution obtained in step 8 to obtain a mixture, ultrasonicate for 1 hour and then stand for 1 hour; 11. Wash the product obtained in step 9 with deionized water and ethanol respectively and dry to obtain the modified catalyst material Co-NC-x for the air cathode, thus completing the preparation of the air cathode catalyst for the microbial fuel cell. (2) Preparation of Co-NC-x cathode electrode and assembly of a single-chamber MFC reactor: The present invention adopts an air cathode single-chamber microbial fuel cell reactor with a volume of 28 mL. The anode uses a fluffy carbon fiber brush with a large specific surface area. The step of pretreating the carbon fiber brush is to soak it in acetone for 24 hours to remove organic impurities on the surface and then rinse it with water and ethanol for multiple times. Finally, it was placed in a muffle furnace and calcined at 450°C for 1 hour to increase the mechanical strength. The composition of the air cathode includes an electron collector, a catalyst layer and a gas diffusion layer. Similarly, the 60-mesh stainless steel mesh used as the current collector was first cleaned with acetone to remove impurities, rinsed with ethanol and water, and placed in an oven to dry for use. Then, the conductive carbon powder and 60% polytetrafluoroethylene (PTFE) dispersion were evenly mixed in ethanol, stirred into a mud-like substance at a mass ratio of 3:7, and then the electrode mud and the stainless steel mesh were pressed together with an electric roller press to form a gas diffusion layer. Then it was placed in a muffle furnace at 340°C and calcined for 20 minutes to melt the PTFE to form a gas mass transfer channel. On the other side, the prepared catalyst and PTFE were mixed together at a mass ratio of 1:1, and the catalyst layer was also pressed onto the stainless steel mesh and dried in an oven using a similar method to the gas diffusion layer. The cathode was cut into discs with a diameter of 30 mm. When assembling the reactor, the gas diffusion layer faces the outside, so that more oxygen can contact the catalyst layer, which is conducive to the reaction.
2. The method for preparing an air cathode catalyst for a microbial fuel cell according to claim 1, characterized in that In step (1)①, the amount of 2-methylimidazole used is 6.72 g, and the amount of deionized water used is 15 mL.
3. The method for preparing an air cathode catalyst for a microbial fuel cell according to claim 1, characterized in that In step (1) ②, the amount of cobalt acetate used is 1.80 g, and the amount of deionized water used is 15 mL.
4. The method for preparing an air cathode catalyst for a microbial fuel cell according to claim 1, characterized in that After stirring for 10 minutes and standing for 5 hours in step (1)④, the product was washed with ethanol 6 times and dried in an oven at 60°C for 12 hours.
5. The method for preparing an air cathode catalyst for a microbial fuel cell according to claim 1, characterized in that The calcination process in step (1) ⑤ is to increase the temperature from room temperature to 700° C. at a heating rate of 3° C. / min and calcine at a constant temperature for 1 hour.
6. The method for preparing an air cathode catalyst for a microbial fuel cell according to claim 1, characterized in that In step (1)⑥, x is 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, and the amount of ethanol used is 5 mL.
7. The method for preparing an air cathode catalyst for a microbial fuel cell according to claim 1, characterized in that In step (1) ⑦, the amount of deionized water used is 60 mL, and the amount of ZIF-67 derived carbon used is 0.1 g.
8. The method for preparing an air cathode catalyst for a microbial fuel cell according to claim 1, characterized in that In step (1)⑧, the amount of deionized water used is 5 mL, and the amount of sodium nitrite used is 0.01 g.
9. The method for preparing an air cathode catalyst for a microbial fuel cell according to claim 1, characterized in that The amount of 0.5M hydrochloric acid used in step (1) ⑨ is 2 mL.
10. The method for preparing an air cathode catalyst for a microbial fuel cell according to claim 1, characterized in that In step (1) (10), the product was washed with deionized water three times and then with ethanol three times, and then dried in an oven at 60° C. for 12 hours.
Citation Information
Patent Citations
Air cathode of microbial fuel cell and preparation method of air cathode
CN104091955A
Graphene loaded Co-N-C oxygen reduction catalyst and preparation method thereof
CN105289695A
Nitrogen-doped carbon material supporting cobalt catalyst and method therewith of catalytic hydrogenation reductive amination to produce amine compounds
CN106552661A
Method for improving stability of fuel cell carbon based electrocatalyst
CN106558708A
Preparation method of Co / C-N catalyst, and applications of Co / C-N catalyst in CO2 hydrogenation synthesis of methanol
CN110280246A
